Evaluasi dan Kajian Penanganan Sampah dalam Mengurangi Beban Tempat Pemrosesan Akhir Sampah di TPA Milangasri Kabupaten Magetan - Yustikarini, Rahmawati; Setyono, Prabang; Wiryanto, Wiryanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Trash has always been an important issue in developing region like in Magetan Regency. Trash handling in Magetan Regency is only undertaken in 63% of its urban areas. Waste generation is increasing whereas landfill capacity is decreasing which implies the need to increase its treatment management. According to the Environmental Office in Magetan district, waste reduction is targeted to be reduced by 10% each year. Only 5500 m2 from 1.6 Ha remains liveable and nowadays landfill capacity is lacking. Based on the calculation of the incoming trash, it is expected that landfill non-availability will prevail in 2018. During composting period, landfill lifetime will have to get procrastinated until 2019 and if mechanism of Reuse, Reduce and Recycle (3R) process is undergoing comprehensively whether through community empowerment or by technological means, then landfill lifetime will take much longer. Landfill overcharge depends primarily on waste generation compacting its volume at sites. Our results show that there is a significant comparison of the volume of untreated incoming trash, with composting technology and 3R mechanism addition. By 2025, the volume of waste in landfill will be 129.030,57 m3 and needing landfill surface 16.129 m2 if waste treatment is not thoroughly undertaken without the help of technological means. During composting process, the volume of waste in the landfill is reduced to 83.869.87 m3 needing an addition of landfill surface amounting 10.484 m2 and much more will it be reduced by 43.811,94 if 3R technology is applied needing 5.476 m2 only of its surface. By using composting technology and 3R mechanism, it is expected that landfill optimization and efficiency will prevail reducing the landfill load while decreasing the pollution level and adding another contribution from renewable energy.